SOSIALISASI CHATGPT UNTUK MEMPERMUDAH PEKERJAAN DINAS PPA PEMPROV DKI JAKARTA - Arrachman, Abdul Kholiq; maesaroh, siti; afiyati, Afiyati; Mubarak, Roy; Kurnia, Rizki Ade (UNIVERSITAS RAHARJA, 2025)
Abstract : ChatGPT is a language model developed by OpenAI, based on the GPT-3.5 architecture. GPT stands for